Localization of Blood Coagulation Factors In Situ in Pancreatic Carcinoma - Wojtukiewicz, Marek Z.; Rucinska, Monika; Zacharski, Leo R.; Kozlowski, Leszek; Zimnoch, Lech; Piotrowski, Zdzislaw; Kudryk, Bohdan J.; Kisiel, Walter (Thrombosis and Haemostasis, 2001)
Blood coagulation is activated commonly in pancreatic carcinoma but the role of the tumor cell in this activation is undefined. Immunohistochemical procedures were applied to fixed sections of 22 cases of resected adenocarcinoma of the pancreas to determine the presence of components of coagulation and fibrinolysis pathways in situ. Tumor cell bodies stained for tissue factor; prothrombin; and factors VII, VIIIc, IX, X, XII, and subunit “a” of factor XIII. Fibrinogen existed throughout the tumor stroma, and tumor cells were surrounded by fibrin. Staining for tissue factor pathway inhibitor, and plasminogen activators was minimal and inconsistent. Plasminogen activator inhibitors -1, -2, and -3 were present in the tumor stroma, and on tumor cells and vascular endothelium. Extravascular coagulation activation exists associated with pancreatic carcinoma cells in situ that is apparently unopposed by naturally occurring inhibitors or the plasminogen activator-plasmin system. We postulate that such local coagulation activation may regulate growth of this malignancy. These findings provide a rationale for testing agents that modulate the blood coagulation/fibrinolytic system (that inhibit tumor growth in other settings) in pancreatic carcinoma.
Keywords: Pancreatic cancer; blood coagulation; fibrin